Efficacy of Osthole in Management of Hypoperfused Retina - Ran Du; Zhao-yang Meng; Jia-lin Wang; Yan-ling Wang (Journal of Ophthalmology)
Purpose. To determine the effect of osthole on the retina in a chronic cerebral hypoperfusion (CCH) rat model and to investigate its therapeutic activity. Methods. Seventy-two rats were randomly allocated into 6 groups. CCH was induced by permanent bilateral common carotid artery occlusion (BCCAO) in five groups. Sham surgery was performed without occlusion of the artery in the sixth group (control group). Animals were administered with saline (model group), osthole (osthole-IG group), aspirin (aspirin group), or ginaton (ginaton group); the osthole-PI group was performed with peribulbar injection of osthole. Four rats in each group were sacrificed every 5 days after drug administration, and histopathology along with morphology of retina were observed. Fundus fluorescein angiography was performed before the animals were sacrificed at day 15. Retinal Akt, NF-κB, Bax, and Bcl-2 levels were assessed using immunohistochemistry, immunofluorescence, and reverse-transcription PCR; retinal injury was assessed using TUNEL in situ; retinal levels of superoxide dismutase (SOD) and malondialdehyde (MDA) were measured. Results. Fundus fluorescein angiography revealed the retinal vascular diameter in the osthole-IG group rats to be wider than that in the model, osthole-PI, aspirin, or ginaton group rats. Histological analysis of retinal tissue revealed an increase in retinal thickness in all treatment groups, and significant improvement was noticed in the osthole-IG group. TUNEL staining revealed fewer apoptotic cells in the osthole-IG and osthole-PI groups than in the other groups. For immunohistochemistry results, in the osthole-IG group, levels of NF-κB and Akt were lower than those in the other treated groups, while levels of the ratio Bcl-2/Bax were higher. Levels of MDA were lower and levels of SOD were higher in the osthole-IG group than in the other groups. Conclusions. Osthole protects the retina from ischemia injury secondary to CCH induced by BCCAO, mainly through anti-inflammatory, antioxidant, and antiapoptotic effects.